Applied Mechatronic: A Sensor-Based Modification of an External Fixator According to Mitkovic - Vladimir Antić; Miodrag Manić; Milan Mitković; Nikola Korunović; Danijela Protić; Radomir Prodanović; Denis Kučević; Gordana Ostojić; Stevan Stankovski (Applied Sciences)
External fixators are frequently used to treat complex fractures with multiple bone fragments and soft tissue injuries. Inaccurate assessment of bone union and premature removal of the fixator may necessitate revisions and prolong treatment. The decision to remove an external fixator typically depends on an orthopedist’s experience. The accuracy of diagnosis can be improved by using a force sensor integrated into the modified external fixator according to Mitkovic. A sensor measuring axial compressive force is mounted between two vertical rods. Experiments with the modified external fixator were carried out using three different axial loads delivered by the universal electromechanical testing machine (UETM) and a sensor that detected the corresponding axial force. Springs with variable rigidity were used to simulate bone callus stiffness. Low rigidity springs represented a high elasticity callus, whereas high rigidity springs represented a callus with lower elasticity. The results show that the force detected by the sensor was nearly identical to the force delivered by the UETM while the callus did not form, decreased as spring rigidity increased, and eventually zeroed out as the leg healed. The findings indicated that using modified external fixator according to Mitkovic can help orthopedists assess bone healing more accurately.